The Analysis of Public Relations Position within an Organization Structure and the Implication of its Role and Function in Various Organizations - Andi Afrilliya Ani; Rachmat Kriyantono; Maulina Pia Wulandari (Sekolah Pascasarjana Universitas Brawijaya, 2017)
The aim of this research are to analysis position of public relations in the organizational structure and the implications of roles & functions in various organizations. The basic concept about public relations role: expert prescriber, problem solving facilitator, communications facilitator and communication technician. This research uses qualitative methods. Informants are public relations of Persada Hospital, public relations of Hotel Santika, public relations of Jatim Park Group, and public relations of Widyagama University. The result of this research shows the position of public relations at Persada Hospital which is directly under the Director of Hospital acting as communication technician role, expert prescriber, communication facilitator, problem solving process facilitator. While the position of public relations in Santika Hotel under seles manager division role as communication technician, proved there are still many bureaucratic levels that must be passed in carrying out its function. The position of public relations Jatim Park Group is under the directors 1 who acts as communication technician role, expert prescriber, communication facilitator, problem solving process facilitator For Widyagama University, the position of public relations is under the direct leader of the highest role as communication technician role and communication facilitator. Performance of public relations relating to the role and position in this study is considered positive and in accordance with the portion of work.Keywords: implications, organizational structure, public relations positions, roles & functionsÂ